Pelvic ring and acetabular fracture: Concepts of traumatological forensic interest. Issue 2 (February 2022) - Basile, Giuseppe; Passeri, Alberto; Bove, F.; Accetta, R.; Gaudio, R.M.; Calori, G.M.
Abstract: Fractures of the pelvic ring and acetabulum generally result after high energy trauma. Pelvic fractures, especially, are considered complex injuries from a therapeutic point of view, in relation to the frequent coexistence of skeletal and / or parenchymal lesions affecting other areas, and the abundant bleeding invariably associated with the latter. The systematic study of these injuries, starting from the 1950s, has led to a significant prognostic improvement, while generally remaining a non-negligible degree of disability. The knowledge of the characteristics of the lesions and of the classification systems, as well as an accurate assessment of the anatomo-functional repercussions, represent therefore the fundamental prerequisites for the correct assessment of physical damage. Herein, we aim to examine whether the medico-legal assessment parameters of physical damage being used in Italy and Europe are appropriate and consistent with the complexity of similar injuries.